Molecular insights for the optimization of solvent‐based selective extraction of ethanol from fermentation broths. Issue 8 (1st April 2013) - Keasler, Samuel J.; Lewin, John L.; Siepmann, J. Ilja; Gryska, Nicole M.; Ross, Richard B.; Schultz, Nathan E.; Nakamura, Masayuki
Abstract : Simulations and experiments were carried out to explore the solvent extraction of ethanol from aqueous solution using a series of seven 10‐carbon alcohols. It is shown that configurational‐bias Monte Carlo simulations in the Gibbs ensemble coupled with the TraPPE‐UA force field can be utilized for predictive screening of the different extraction abilities (in terms of capacity factor and selectivity) of these alcohols. Analysis of the simulation trajectories indicates that extraction capacity is connected to the stabilization of larger ethanol/water cluster in the organic solvent, whereas selectivity is improved when smaller ethanol/water clusters are more prevalent. © 2013 American Institute of Chemical Engineers AIChE J, 59: 3065–3070, 2013